Love and Duty: Translating Films and Teaching Online Through a Pandemic - Christopher Rea (Global Storytelling)
The Chinese Film Classics project, launched in 2020, is an online research and teaching initiative aimed at making early Chinese films and cinema history more accessible to the general public. Led by Christopher Rea at the University of British Columbia, the project is centered on the website http://chinesefilmclassics.org and the companion YouTube channel Modern Chinese Cultural Studies. These two platforms together host new English translations of over two dozen Republican-era Chinese films, over two hundred film clips organized into thematic playlists, and a free online course of video lectures on Chinese film classics. This essay tells the story of how the Chinese Film Classics project grew from being a book project into a multiplatform translation, teaching, and publication project during the COVID-19 pandemic. Online teaching and social media publication involved multiple global storytellers: filmmakers, educators, translators, students, and the broader Internet public. How might moving things online change, or improve, the practice of cultural history? Rea highlights in particular the practical considerations facing the translator and gives examples of how, in a social media context, some of the stories are told not by creators and audiences but by data analytics.